An Analysis on the Factors for Cervical Insufficiency Causing Adverse Emotions Among Pregnant Women at Different Gestation Phases - Wu, Qichang; Chen, Jiebing; Zou, Qiaojian; Zeng, Xun; Yang, Yan; Zhou, Yijia; He, Guimei; Luo, Chunqi; Wu, Fengchun (Frontiers in Psychiatry, 2022)
Background To analyze the anxiety, depression, and related factors among pregnant women with cervical insufficiency, so as to provide a reference for clinical psychological intervention as an adjuvant therapy. Methods A total of 101 cases in China with cervical insufficiency were included in the observation group by a convenience sampling method, and 114 normal healthy women of childbearing age were selected as the control group. Participants were investigated and observed for anxiety and depression by SAS and SDS, respectively, to analyze the emotional state and influencing factors of the patients with cervical insufficiency. Stratified by the first, second and third trimesters, our study used whether depressive or not and whether anxiety or not as the dichotomous variables. A multivariate Logistic regression was adopted to analyze the influencing factors. Relevant influencing factors were screened out by the forward stepwise method in combination with professional knowledge and the number of variables. Results There were statistical significant differences in SAS and SDS between observation group and control group and the incidence rate of anxiety and depression was higher in pregnant women with CI. Multivariate Logistic regression demonstrated that history of abnormal pregnancy was the main influencing factor for anxiety and depression in the early and middle gestation phases, and cervical insufficiency was the factor influencing the anxiety in early gestation and both anxiety and depression in the late gestation phase. Conclusion Cervical insufficiency may have a negative impact on the emotions of pregnant women. Individualized and targeted mental care should be added into clinic work to prevent negative outcomes.